2017
DOI: 10.1038/srep42974
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-transport Spectroscopy of the First and Second Two-dimensional Subbands in Al0.25Ga0.75N/GaN Quantum Point Contacts

Abstract: Magnetic transport spectroscopy is investigated in quantum point contacts (QPCs) fabricated in Al0.25Ga0.75N/GaN heterostructures. The magnetic field perpendicular to the two-dimensional electron gas (2DEG) is shown to depopulate the quasi-one-dimensional energy levels in the first two-dimensional (2D) subband faster than those in the second one. In GaN based heterostructures, the energy levels in the second 2D subband is generally concealed in the fast course of depletion and hence rarely detected. The perpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…2d) where a weak structure in the middle signals the QWS 2 . Our observation of QWS 2 is consistent with its recent detection via magneto-transport spectroscopy 24 . The presence of this state centered further away from the interface compared to the QWS 1 indicates that V(z) in the GaN-HEMTs has a long-range saturated shape (see the model in Fig.…”
Section: Resultssupporting
confidence: 92%
“…2d) where a weak structure in the middle signals the QWS 2 . Our observation of QWS 2 is consistent with its recent detection via magneto-transport spectroscopy 24 . The presence of this state centered further away from the interface compared to the QWS 1 indicates that V(z) in the GaN-HEMTs has a long-range saturated shape (see the model in Fig.…”
Section: Resultssupporting
confidence: 92%
“…However, due to its relatively large value, the subband excitation energy is not easily accessible; see Ref. 35 for an example of its determination in a transport measurement. We illustrate these points in Fig.…”
Section: (α)mentioning
confidence: 99%
“…[33][34][35][36][37] However, g-factor is not isotropic . 32,[38][39][40] Thus far, only a few conductance measurements in the presence of outof-plane magnetic fields are conducted to date , 36,[41][42][43][44][45][46][47][48] and there is a paucity of reports on double-layer QPCs. In the experiments above, enhancements in g-factor were reported that deserved theoretical attention .…”
Section: Introductionmentioning
confidence: 99%